(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Wheelchair racing gloves are often hand crafted from thermoplastics. The geometries are unique to the individual, often with thumb or finger cavities rendering line-of-sight laser scanning techniques inappropriate for full digital capture. This study describes the use of micro-CT to reverse engineer the bespoke hard gloves of an elite Paralympic athlete, with fabrication via 3D printing. Subsequent design changes, combined with the identification and manipulation of key process parameters during material extrusion, have demonstrated this approach affords enhanced glove performance. Preliminary rolling road test results suggest a competitive advantage for the athlete. The approach is believed transferrable within physical rehabilitation.